The role of b-cell keratins in islet histology, glucose uptake, and diabetes susceptibility - Kosijer, Petar (My University, 2023)
β-cells along with several types of other cells compose the endocrine pancreas and they produce the hormone insulin which has a role in the regulation of glucose in the bloodstream. A disruption in insulin production and its secretion in β-cells causes diabetes. Keratins (K) are members of the intermediate filament protein family and they are known for both mechanical and physiological activity in cells. Their role is emphasized by 80 human diseases caused by keratin filament mutations. The most common types of keratins in the endocrine pancreas are K8 and K18 and the global K8 knockout in mice leads to the mislocalization of glucose transporter 2 (GLUT2). Three aims were set for this thesis: evaluate the connection between keratins and proliferation in β-cells, study the role of keratins in β-cells during streptozotocin-induced diabetic stress, and understand the role of keratins in β-cells during glucose uptake. Histology analysis showed that bigger islets are present in β-cell-specific K8 knockout mice compared to the wild type. The analysis of β-cell proliferation-related parameters showed no difference in these mice compared to the control. Digital and quantitative histological analysis of the samples from short-term streptozotocin-treated mice showed the K8 conditional knockout mice have lower islet damage compared to the control and were thus, less susceptible to this diabetic model. No differences were seen in islet size, islet mass, and islet number in streptozotocin-treated mice compared to control. GLUT2 localization analysis showed that in β-cell-specific K8 knockout mice GLUT2 gets mislocalized from the membrane to the cytoplasm compared to the control mice. The assessment of the damage score and GLUT2 localization analysis showed that keratins might have a role in the targeting of β-cell GLUT2 since streptozotocin is transported into beta cells through GLUT2.
Keywords: keratins, endocrine pancreas, glucose transporter 2, streptozotocin, proliferation